Einzelhandelsstandorte des Verdichtungsraumes Leipzig im Spannungsfeld zwischen kommunaler Entwicklung und räumlicher Ordnung - Den Hartog-Niemann, Eva; Boesler, Klaus-Achim (ERDKUNDE, 1994)
Some large cities in the new federal states of Germany are experiencing unexpected problems in the wake of the transformation process from a command economy system to one of a market economy. In what follows the interaction of retail location development, town development, state planning and regional planning will be presented through the chain of effects set off by the development of the retail trade in Leipzig after 1989. With only 84,000 m2 available for retailing, the centre of Leipzig is faced with building applications for a fifteen-fold increase in the retail area, most of which is in unintegrated locations in the outlying districts. This raises a multitude of problems: Shopping centres on greenfield sites lead to a considerable loss of purchasing power. The town centre is increasingly losing its attractiveness; this in turn inhibits housing construction, as well as the urgently needed preparedness of commerce and gastronomy to invest in the redevelopment. In the prefabricated residential quarters the emerging social segregation of the population holds considerable potential for conflict. The infrastructure of transport is so far in no way able to cope with the changed shopping behaviour of the city's inhabitants. The shopping centres are largely planned for, if not already built on, villages in outlying districts lacking any central function. This proves to be a particular impediment to the setting-up and implementation of a central place concept. In the first two years after die Wende (the Change) the concerns of spatial planning were hardly taken into account at all, since relevant laws did not exist. This results in a lack of communal agreement, and thus in an extreme concentration of retail areas, especially along the radial routes from the city to the surrounding rural district of Leipzig. In the early years after the Wende facts were created which, going far beyond mere retail trade development, are bound to present considerable problems for the development of the Leipzig conurbation.